PERKEMBANGAN PSIKOLOGI ANAK USIA DINI Di KELOMPOK BERMAIN AL-FIRDAUS BAHRUL ‘ULUM TAMBAKBERAS JOMBANG - Safitri Devi Agustin; Hilyah Ashoumi (JoEMS (Journal of Education and Management Studies), 2019)
This study aims to determine the Psychology of Early Childhood in the Al-Firdaus Bahrul ‘Ulum Play Group. Where the development of psychology of career girls and non-career women is experiencing delays and efforts of teachers in improving the development of early childhood psychology. The development of psychology of career girls is influenced by parenting. If parents are able to manage me time with a good child, the child's development will be maximal. in addition, the development of psychology for non-career girls is equally influenced by parenting. But the difference lies in the child's future. If a career female child is on average independent, but a non career female child is spoiled and wants to win on her own. Teachers' efforts to improve early childhood development are through activities or learning that meet 6 aspects of development. With these activities it will reduce the anxiety experienced by parents, especially career women for the development of the children.